2013
DOI: 10.6061/clinics/2013(04)18
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training prior to myocardial infarction attenuates cardiac deterioration and cardiomyocyte dysfunction in rats

Abstract: OBJECTIVES:The present study was performed to investigate 1) whether aerobic exercise training prior to myocardial infarction would prevent cardiac dysfunction and structural deterioration and 2) whether the potential cardiac benefits of aerobic exercise training would be associated with preserved morphological and contractile properties of cardiomyocytes in post-infarct remodeled myocardium.METHODS:Male Wistar rats underwent an aerobic exercise training protocol for eight weeks. The rats were then assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
1
21
0
2
Order By: Relevance
“…Aerobic exercise is a non-pharmacological and effective way to protect the heart against aggression and insult (Portes & Tucci 2006); however, there are studies that found no benefits to this condition (Veiga et al 2011(Veiga et al , 2013. The preventive training protocols for acute myocardial infarction were performed for an average of 8 weeks, which was the period used in the present study (Freimann et al 2005;Bozi et al 2013;Veiga et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerobic exercise is a non-pharmacological and effective way to protect the heart against aggression and insult (Portes & Tucci 2006); however, there are studies that found no benefits to this condition (Veiga et al 2011(Veiga et al , 2013. The preventive training protocols for acute myocardial infarction were performed for an average of 8 weeks, which was the period used in the present study (Freimann et al 2005;Bozi et al 2013;Veiga et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies suggest that chronic aerobic physical training applied in a preventive manner in acute myocardial infarction promoted improvement in cardiac function and survival (Waard & Duncker ; Bozi et al . ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, a recent study (72) failed to confirm the benefits of exercise-based rehabilitation. Besides the investigation of therapeutic effects of exercise on the remodeling process after MI, more recently, researchers have become interested in the effect of endurance training before MI and reported protective but also neutral effects (5,7,12,70,75).…”
Section: Our Data Provide New Insights Into the Exercise-mediated Carmentioning
confidence: 99%
“…In one study with animals, exercise pretreatment preserved cardiomyocyte contractile and morphological properties, which played a crucial role in cardioprotection against cardiac structural deterioration and dysfunction caused by MI (Bozi et al, 2013). Exercise pretreatment could also reduce collagen accumulation, thicken infarcted wall, alleviate MI volume, improve muscle strength, enhance responsiveness to calcium, and preserve cardiac myocyte shortening; it could also improve the maximum relengthening and shortening velocities in infarcted hearts of rats (Bozi et al, 2013;Ciolac et al, 2014). There was a close relationship between cardio protection against myocardial injury induced by exercise pretreatment and cardiac natriuretic peptide receptor B (NPR-B) and C-type natriuretic peptide (CNP) (Lu and Pan, 2017).…”
Section: Different Exercise Time and MI The Benefits Of Exercise Intementioning
confidence: 99%